Happiness and dishonesty budgeting: An experimental study - Purnama, Ida Ayu; Hardiana, Shely Rizki; Simanjuntak, Oliver Samuel (Department of Accounting, Faculty of Business, Universitas PGRI Yogyakarta, 2024)
Budgeting is crucial in organizations because it is used as a monitoring and evaluation tool. A poor performance climate encourages individuals to work effortlessly so research is needed that links good mood to budgeting. The research implies that organizations can build a positive work climate to reduce slack rather than just focusing on formal regulations and threats. The purpose of the study is to examine the effect of differences in budget setter mood on proposal preparation regarding the intention to create slack in the budget. The results show that individuals in a happy mood will create less slack in the budget. Individuals in a happy mood will create less slack because the work climate influences a person to make decisions. Individuals in a good work environment will be motivated to be honest. The originality of this research is different from previous research, namely dividing the mood into 2 parts, happy mood and sad mood with the context of individual budget settings, not divisions.